Modelo de acompañamiento remoto parental para favorecer la autonomía en niños de 4 años Programa Tutores de Acogida, Lambayeque-2020 - Lozano Segobia, Nalda Yamari (2022)
The purpose of this research is to study the model of parental remote accompaniment focused on the autonomy of four-year-old children, as we know the family are the primary agents in the development of children and since they are the ones who manage to promote the development of autonomy through activities carried out at home. That is why, in order to carry out the necessary study about our research, an interview through telephone calls with the parents of the children in the four-year extended classroom of an educational institution of the University had to be used as an instrument. Lambayeque region, the items used in said interview were aimed at designing the remote accompaniment model proposal based on the determination in the following dimensions, the first dimension called trust, a level reached of 93% was obtained, located in the medium level, while that 7% managed to place themselves in the high level. In the dimension called initiative, it was determined that a percentage of 87% was found at the medium level, with 13% of the children being at a high level. Finally, in the diligence dimension, it was possible to determine that 93% of the 4- year-old children were found in the medium level, however, 7% were located in the high level, with 0% of the children being at the low level; All these percentages obtained led to the realization of the proposal of the parental remote accompaniment model through which, through the planning of twenty activities, it is sought to promote and reinforce the development of the autonomy of four-year-old children.